Innovating Coffee Production: Integrating Anaerobic Carbonic Maceration Technology to Achieve International Standards - Dyah Kusuma Wardani; Ratih Puspitorini Yekti Ambarkahi; Raden Roro Lia Chairina; Paramita Andini; Dhanang Eka Putra (Smart Society, 2024)
In the coffee industry, product quality is a key factor in competing in the international market. The Teaching Factory (TEFA) at Polije faces challenges in maintaining quality consistency and meeting international standards. This study aims to implement Anaerobic Carbonic Maceration (ACM) technology in the coffee fermentation process at TEFA Polije to enhance the quality of the produced coffee. The methods used include technical training for workers on the operation and maintenance of ACM technology, the application of strict quality protocols, and the optimization of the logistics system from raw material management to product distribution. Data were collected through sensory evaluation and interviews with workers. The results indicate that the implementation of ACM technology significantly improves the coffee’s aroma and flavor profile, as well as the consistency of bean texture, aligning with international standards. The evaluation shows that 80% of workers were able to operate the technology correctly, and 75% of the products met premium standards after implementation. The conclusion of this study is that ACM technology is effective in improving the quality of TEFA Polije coffee while also creating opportunities for expansion into the international market.